KONSEP ADIL DALAM HUKUM WARIS ISLAM - Fadlih Rifenta (Tamaddun, 2018)
The science which is lost first among muslim community is the knowledge of inheritance as Rasulullah had been explained. Moreover, there are some efforts to destroy the inheritance law arrangement in islam. By the opinion that the division of inheritance that for son is equal with two daughters is a form of injustice toward woman. Therefore, it is allowed to create modification for Islamic inheritance law. This paper tries to explain the justice concept in Islamic inheritance law. By the conclusion that, First ; the definition of Islamic inheritance law has to follow the determination by Allah SWT and it does not mean that equal division is equal quantity. Second; in the case of inheritance division in islam, it contains the universal justice according to theology, economic and social.